Suscetibilidade in vitro de Conidiobolus lamprauges frente a fármacos antimicrobianos - Stefanello, Josias da Rosa (2018)
Conidiobolomycosis is an important and difficult-to-treat infection. The disease is caused by the fungi Conidiobolus coronatus, C. incongruus and C. lamprauges, affecting sheep, horses, dogs and humans. There is no common understanding about the ideal antifungal therapy for the infection treatment. Assessment of antifungal susceptibility is one way of monitoring resistance and predicting appropriate therapies. Therefore, the present study assessed the sensibility of seven isolates of C. lamprauges considering the antifungal drugs Amphotericin B, voriconazole, miconazole and terbinafine, the antibacterial drugs sulfamethoxazole + trimethoprim, azithromycin and dapsone and the antiprotozoal drug miltefosine, in an isolated an in association manner, through the checkerboard method, by means of the broth microdilution method, which is standardized by the M38-A2 document, of the Clinical and Laboratory Standards Institute (CLSI). In an isolated way, the minimum inhibitory concentrations (MICs), for Amphotericin B, vary in 0.25-1.0 μg/mL, to miconazole 2.0-8.0 μg/mL, to terbinafine 0.25-2.0 μg/mL, to voriconazole 512 μg/mL, to sulfamethoxazole + trimethoprim, 32/6.4-256/51.2 μg/mL, azithromycin >64, to dapsone >32 μg/mL and to miltefosine 2-16 μg/mL. Higher rates of synergism were observed in the combinations of miltefosine + azithromycin (100%), miltefosine + dapsone (100%), azithromycin + dapsone (85.7%). The most relevant associations deserve attention as candidates for Conidiobolus spp. infection treatment. Hence, further in vitro and in vivo studies with a wide range of clinical isolates and different Conidiobolus spp. are needed to better understand the susceptibility to the antimicrobials described in this study.